Facilitating gender transformation in livestock management through Community Conversations in Bide community, Ethiopia - Dessalegn, Bezaiet; Woldegiorgis, Mamusha (International Center for Agricultural Research in the Dry Areas, 2023)
According to Interagency Gender Working Group (IGWG), “Gender transformative approaches actively strive to examine, question, and change rigid gender norms and imbalance of power … Gender-transformative approaches encourage critical awareness among men and women of gender roles and norms; promote the position of women; challenge the distribution of resources and allocation of duties between men and women; and/or address the power relationships between women and others in the community” (Rottach et al. 2009). Gender transformative programs thus aim to move beyond interventions with specific groups of recipients to change the broader social norms and structures that shape gender inequality (Barker et al. 2007). A fundamental principle in a gender transformative approach is the recognition that gender is socially constructed and that it involves a process that goes beyond the individual, the household, or women only to changes in perceptions, attitudes, values, and expectations that shape social relations; as well as the rules, norms and practices that govern them (Morgan 2014). Therefore, measuring a project’s contribution to gender transformation requires a different lens to capture the wider change process that goes beyond women empowerment indicators that mainly focus on increases in their ability to achieve specific changes in their behavior or access (Greene and Levack 2010). Gender norms are often reflected in the “informal, implicit rules that govern what a person can and cannot do in the pursuit of daily life” (Fehr and Gachter 2000). Gender transformative programs attempt to measure less tangible changes, such as changes to an individual’s attitudes, values, beliefs, and expectations about gender…. Changing both men’s and women’s gender-related attitudes are key to the process of achieving gender equality and need to be captured. To adequately measure gender transformation, programs also need to identify the multiple scales in which gender norms are produced and operate; and involve the larger community or society at large (Rottach et al. 2009). Addressing constraining gender norms and practices requires dialogues to change knowledge, attitudes, and practices (KAP) of community members and service providers. Community Conversations create inclusive spaces for dialogue, joint analysis, collaborative learning, and action, which facilitate changes in the KAP of community members and local service providers. Through dialogue and collaborative learning processes, the underlying gender values and norms that shape the behaviors and attitudes of community members and service providers as well as the patterns of interactions between women and men can be explored and addressed in livestock development. Community Conversations (CCs) offer unique opportunities to facilitate dialogue among groups of a community and key local government and research institutions on selected topics of interest. Initiated through a joint ICARDA-ILRI effort and building on the Community Based breeding program (CBBP), CCs were conducted in several districts in northern and southern Ethiopia to, inclusively and collectively, identify key challenges in the management and marketing of sheep; facilitate group learning and joint analysis; and seek context-specific solutions to address them. Common topics of the CCs included community breeding, feed production and management, animal upkeep and health, antimicrobial use and resistance, marketing, and gender roles. The CCs were subsequently complimented with the organization of Communities of Practice (CoP) that comprised representatives of woreda-level experts in selected fields of practice including – agriculture, livestock, gender, natural resource management, animal health, socioeconomics, extension, communication, and others as needed. The CoPs created space for woreda-level inter-disciplinary dialogue, peer-learning, project and resource coordination, and promotion of integrated context-specific solutions that are in line with woreda and regional strategic plans. Multiple topic-specific modules have been developed over the years to support facilitators of CCs, as well as reports on the outcomes of the conversations held.